Micropropagation for Rapid Multiplication of Planting Material in Cassava (Manihot esculenta Crantz) - R, Shiji; George, James; S, Sunitha; R, Muthuraj (JOURNAL OF ROOT CROPS, 2015)
Rapid multiplication of planting material in cassava through tissue culture techniques such as shoot initiation, micropropagation and hardening was studied in cassava variety Sree Padmanabha. The effect of nodal segments from axillary bud of the field grown cassava cultured in Murashige and Skoog’s basal medium supplemented with different concentrations and combinations of 6- Benzylaminopurine (BAP) and Naphthalene acetic acid (NAA) were evaluated based on different parameters viz., number of shoots, number of roots, number of leaves and number of nodes. Minimal risk of contamination was observed with sterilization in 0.1% HgCl2 for 7 min, which was found to be an effective surface sterilant. For in vitro regeneration using apical node as explant, MS media with 0.3 mg l-1 NAA was found to be the best in terms of shoot having three nodes. When in vitro shoots were inoculated in MS media with 0.1 mg l-1 NAA, rooting was the most profuse. Nodal explants took one month for development into plantlets having three nodes. Potential number of planting material production from one nodal explant using micropropagation techniques was estimated to be ranging from 16,000 to 17,000 in one year period. Well rooted in vitro plantlets in sterilized vermiculite with 4-5 cm length were found suitable for hardening and subsequent transplanting, which gave 91% success after two months of hardening.